PELATIHAN PENINGKATAN KUALITAS KEMASAN DAN PEMASARAN DIGITAL UMKM DESA KARANGKEMIRI JERUK LEGI - Wulansari, Nuni; Kharismawati, Annissa Dwi; Ayunintyas, Ikhsanti Diah; Saputri, Natasya Bella (Aspirasi Masyarakat, 2025)
This community service activity aims to improve the quality of packaging and digital marketing capabilities for MSME players in Karangkemiri Village, Jeruk Legi District, Cilacap Regency. This training was motivated by the low competitiveness of local products due to unattractive packaging and limited use of digital technology in promotion. The community service activity was held on August 7-8, 2025, and was attended by 21 SMEs in Karangkemiri Village, Jeruklegi, Cilacap Regency. The community service team consisted of a cross-institutional collaboration between Universitas Al-Irsyad Cilacap, Pemerintah Kecamatan Jeruklegi, Kelurahan Karangkemiri, Badan Narkotika Nasional Kabupaten Cilacap, Dinas Perdagangan, Koperasi Usaha Kecil dan Menengah Cilacap, Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu. The community service methods included socialization, technical training on packaging design, and assistance in using social media. The results of the activity showed that the 21 MSME participants who took part in this activity were able to understand the principles of effective packaging design, such as aesthetics, functionality, and product identity, and began to implement digital marketing strategies through social media. This activity made a real contribution to building the capacity of local MSMEs to be more adaptive to the demands of the modern market. This community service activity can be a model for the development of innovative and highly competitive village MSMEs.